Cytotoxic effects induced by combination of heliantriol B2 and dequalinium against human leukemic cell lines - Vela Gurovic, Maria Soledad (2011)
Natural occurring compounds are considered an important source of antitumoral agents. In the present study, the cytotoxic potential of three pentacyclic triterpenes isolated from Chuquiraga erinacea (Asteraceae), against the human leukemic cell lines NB4 and K562 was assessed. Heliantriol B2 (HB2) showed the highest cytotoxic activity after 24 h treatment showing IC 50 values of 1.98 ± 0.12 μm and 3.52 ± 0.14 μm for NB4 and K562 cells, respectively. This activity was higher than that of the reference compound dequalinium (DQA). Apoptosis and necrosis induced by HB2 in both NB4 and K562 cell lines were analysed by Annexin V/PI labeling. Mitochondrial alterations including reactive oxygen species (ROS) production and mitochondrial transmembrane potential (Δψm) were also tested. The results demonstrated that HB2 induced cell death by apoptosis and necrosis and showed enhanced cytotoxic effects in combination with DQA. Besides, HB2 induced ROS overproduction in NB4 cells and a slight decrease of Δψm. Consequently, our findings prompt further studies on the HB2 mechanism of action and its selectivity to tumor cells in order to assess the potential of HB2 as an agent for cancer treatment. Copyright © 2010 John Wiley & Sons, Ltd.